Prevalence of type 2 diabetes risk factors, including overweight and obesity, among youth attending hospital‐based paediatric care in Western Melbourne. (25th November 2022) - Angley, Eleanor; Matejin, Emily; Gul, Saba; Rodda, Christine; Longmore, Danielle K
Abstract : Aim: To determine the prevalence of risk factors for type 2 diabetes in overweight and obese adolescents attending hospital‐based paediatric care in Western Melbourne. Methods: One hundred overweight and obese adolescents (aged 10–17 years) who attended an outpatient clinic at Sunshine Hospital between May 2019 and May 2020 were randomly selected following a retrospective chart review of 10–17 years old for whom a height and weight had been documented. Additional risk factors for type 2 diabetes were ascertained via structured telephone interview. Data were analysed to determine the overall prevalence of risk factors for type 2 diabetes, and to evaluate for associations between each parameter with body mass index and the number of risk factors. Results: Of the 487 adolescents who had height and weight data recorded, 45% were overweight or obese. 77% of those who were interviewed had an additional risk factor for type 2 diabetes. No association between the number of risk factors and body mass index standard deviation score was found. Additionally, there was no association between the number of risk factors for type 2 diabetes and either family history of type 2 diabetes or ethnicity. Conclusions: This paediatric subpopulation had a high rate of risk factors for type 2 diabetes in addition to overweight and obesity, and are at risk of premature mortality and chronic morbidity should they develop type 2 diabetes.